Cardioprotective effects of Plinia cauliflora (Mart.) Kausel in a rabbit model of doxorubicin-induced heart failure. (5th October 2019) - Romão, Paulo Vitor Moreira; Palozi, Rhanany Alan Calloi; Guarnier, Lucas Pires; Silva, Aniely Oliveira; Lorençone, Bethânia Rosa; Nocchi, Samara Requena; Moura, Cátia Cristina de Freitas Sari; Lourenço, Emerson Luiz Botelho; Silva, Denise Brentan; Gasparotto Junior, Arquimedes
Abstract: Ethnopharmacological relevance: In Brazil, the fruit of a native species that is popularly known as "jabuticaba" ( Plinia cauliflora [Mart.] Kausel) is widely consumed fresh or used for the production of liqueur, juice, and jelly. In Brazilian folk medicine, this species is used to treat asthma, throat inflammation, and gastrointestinal and cardiovascular disturbances. However, no previous studies have reported its cardioprotective effects. Aim: To evaluate the possible cardioprotective effects of a hydroethanolic extract of Plinia cauliflora (EEPC) in female rabbits in a model of doxorubicin-induced heart failure. Material and methods: EEPC was obtained and fractionated by solid phase extraction, and its constituents were determined by liquid chromatography coupled to diode array detector and mass spectrometry (LC-DAD-MS). Thirty female New Zealand rabbits received doxorubicin administration for 6 weeks to induce heart failure. EEPC was orally administered at doses of 75 and 150 mg/kg daily for 42 days. Enalapril (5 mg/kg) was used as a reference cardioprotective drug. At the end of the experimental period, blood pressure and heart rate were recorded. Serum parameters, including lipid profile, troponin, creatinine, nitrotyrosine, malondialdehyde, nitrite, and brain natriuretic peptide, were measured. The electrocardiographic profile and renal vascular reactivity were evaluated. Cardiac histopathology and ventricular morphometry were performed, and the tissue enzymatic antioxidant system was investigated. Results: A total of 37 compounds were detected in EEPC, including organic acids, phenolic acid derivatives, flavonoids, anthocyanins, and hydrolysable tannins (gallotannins and ellagitannins). EEPC treatment induced a cardiorenal protective response, prevented hemodynamic and functional alterations, and prevented ventricle remodeling. These effects were associated with the normalization of creatinine and brain natriuretic peptide levels and modulation of the tecidual antioxidant defense system. Conclusion: The present study demonstrated that EEPC may prevent doxorubicin-induced heart failure by modulating the antioxidant defense system, reducing reactive oxygen species-induced damage, preventing alterations of hemodynamic and endothelial function, and preventing damage to the cardiac structure. EEPC, especially at the highest dose tested, may be considered a cardioprotective coadjuvant to prevent doxorubicin-induced cardiotoxicity. Graphical abstract: Image 1